2023
DOI: 10.1101/2023.05.17.540956
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide association and environmental suppression of the mortal germline phenotype of wildC. elegans

Lise Frézal,
Marie Saglio,
Gaotian Zhang
et al.

Abstract: The animal germline lineage needs to be maintained along generations. However, some Caenorhabditis elegans wild isolates display a mortal germline phenotype, whereby the lineage becomes sterile after several generations at 25C. We used a genome-wide association approach to study the genetic basis for this phenotype in C. elegans populations. We detected a significant peak on chromosome III around 5 Mb, which was confirmed using introgression lines. These results indicate that a seemingly deleterious genotype i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…These studies revealed multiple features of the microbiota in C. elegans natural habitat and their relationship to host physiology (Dirksen et al, 2020;Zhang et al, 2017). Studying bacterial species that are naturally associated with C. elegans might reveal processes that occur in the wild, and not in the laboratory, and vice versa; for example, bacteria from C. elegans' natural environment suppress mortal germline phenotypes that wild worms exhibit on laboratory strains of E. coli (Lise Frézal et al, 2023). Therefore, it is important to test the physiological relevance of laboratory experimental results under more natural conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These studies revealed multiple features of the microbiota in C. elegans natural habitat and their relationship to host physiology (Dirksen et al, 2020;Zhang et al, 2017). Studying bacterial species that are naturally associated with C. elegans might reveal processes that occur in the wild, and not in the laboratory, and vice versa; for example, bacteria from C. elegans' natural environment suppress mortal germline phenotypes that wild worms exhibit on laboratory strains of E. coli (Lise Frézal et al, 2023). Therefore, it is important to test the physiological relevance of laboratory experimental results under more natural conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the effect of bacterial environments on C. elegans susceptibility to OrV. We focused on monocultures of bacterial clones isolated from C. elegans natural habitats (13,14,15,36,37). Our objective was to determine whether the bacterial environment affects the nematode's response to the virus and gain a deeper understanding of how specific bacterial strains may modulate host susceptibility to viruses.…”
Section: Introductionmentioning
confidence: 99%